(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
The present research is aimed at enhancing solubility and drug dissolution of clopidogrel (CPG) used as oral antiplatelet agent by employing solid dispersion (SD) technique. Total 40 SDs formulated with drug: polymers (pluronic F127, poloxamer 407, labrafil PG, PEG 6000, gelucire 50/13), in varying ratios (1:0.5, 1:1, 1:2, 1:3, 1:4) of which CPG1 to CPG20 and CPG21 to CPG40 prepared by adopting solvent evaporation method fusion (melt) method respectively. The formulation CPG40 containing pluronic F127 as polymer showed highest solubility of 6.57±0.04 mg/ml) that is 45 folds than pure drug. Similar results reflected in the dissolution studies where CPG40 containing CPG: pluronic F127 in 1:4 ratio showed maximum % drug content, % practical yield and drug dissolution of 99.14% in 60 minutes when compared with other formulations and pure drug (32.76%) obtained by fusion melt method. From FTIR studies the optimized formulation CPG40 showed the compatibility between drug and polymers. XRD and SEM studies showed CPG40 exists in amorphous form that fetched in better drug release from the SD formulation in comparison to pure drug.